Factors affecting the performance of security units (security guard) in Balikpapan city - Pudjiati Pudjiati; Tutik Yuliani (Faculty of Economics and Business Mulawarman University, 2022)
The research method used is descriptive quantitative research. The object of this study is a security guard who works in several companies in Balikpapan City with a total of 138 respondents. The analytical technique used is multiple linear regression analysis by using the F test and t test. The variable used in this study is the dependent variable, namely, Employee Performance (Y), and the independent variables consists of : Training (X1), Discipline (X2), and Work Environment (X3). The results of this study show that, either simultaneously or partially, the variables of Training, Discipline and Work Environment had a significant influence on Employee Performance, where the Training variable had a dominant influence on Employee Performance.